Estudio cualitativo de la vorticidad en 3D en el modelo ahmed : análisis de la topología de la vorticidad en un flujo estacionario alrededor de un vehículo tipo ahmed (2016)
This undergradute thesis is focused on vehicular Aerodynamics, specifically on the study of the vorticity lines that exist around the Ahmed model of a vehicle as it interacts with a flux of air. The main objective of the project is to understand how the vorticity field distributes and how it evolves to form the complexities present in the wake of the vehicle. This project is the second part of the study as it only focus on the 3-D vorticity on the body of the vehicle without the wake, however it allows to understand further the natur of the velocity field in the wake, the first approach in 2-D was realized by the student Segio Lobo in his undergraduate thesis. The work was divided in two major components that lead to the results; the first one is a computational aspect, in which an algorithm in Wolfram Mathematica and in Matlab...